Interaksi Etnik Lokal dan Pendatang: Studi Tentang Perubahan Struktur Keluarga di Kota Bengkulu - Rifa'i Rifa'i; Ayu Wijayanti; Hafri Yuliani (Universitas Andalas, 2022)
This study aims to analyze the interaction between ethnic groups and changes in the family structure of the Minangkabau, Javanese, and local ethnic groups in Bengkulu City. This research uses a qualitative approach with an analytical descriptive method. The results of the study explain that: First, the interaction pattern carried out by each ethnic Javanese, Minang and local ethnic is an associative interaction, where the interaction that arises is the self-awareness of each ethnicity of the importance of the meaning of life interacting without having to contradict even though different ethnicity or ethnicity they come from. In fact, in the local people's life, even though they live side by side with multi-ethnic groups, there has never been friction or inter-ethnic conflict. Second, in the Minang ethnic there is a trend to change the kinship system from matrilineal to bilateral kinship system, as result there is also a shift in the role of the powerful and responsible from uncle to father who is in charge and responsible for the family. Thirdly, in Javanese, no fundamental change finding, but the change lies only in the calling of everyone in the family.